EFFECT OF NITROGEN AND PHOSPHORUS ON VEGETATIVE GROWTH AND FLOWER YIELD OF CHRYSANTHEMUM (CHRYSANTHEMUM MORIFOLIUM) CV. NILIMA - CHAWLA, S.L.; MOHAMMED, S.; MAHAWER, L.N.; JAIN, M.C. (Annals of Agricultural Research, 2014)
The effect of four levels of N (0, 150, 300 and 450 kg ha-1) and P (0,150, 300 and 450 kg ha-1) on growth, flowering and yield of chrysanthemum cv. ’Nilima’ was investigated in factorial randomized block design with three replications at Horticulture Farm, Rajasthan College of Agriculture, MPUAT, Udaipur. Results reveated that application of nitrogen and phosphorus @ 300 and 150 kg ha-1, respectively in chrysanthemum cv, Nilima proved to be the optimum doses for obtaining higher flower yield ha-1.